Optimization of Phenolic and Flavonoid Extraction in Lavandula Angustifolia using Ultrasonic Assistance Extraction - Della Ananda; Andi Ika Julianti; Tubagus Akmal (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2025)
Lavender contains active compounds such as flavonoids, tannins, coumarins, phytosterols, and minerals, which possess antioxidant properties and pharmacological potential. This study optimized the extraction process of lavender flowers to maximize bioactive phenolic and flavonoid yields. Ultrasonic-assisted extraction (UAE) was employed, and optimization was conducted using a Box-Behnken design in Design Expert 13.0.5.0 software. The influence of ethanol concentration, liquid-solid ratio (LSR), and extraction time on total phenolic content (TPC) and total flavonoid content (TFC) was evaluated. Results revealed that LSR significantly impacted the responses. Optimal conditions were determined as an LSR of 50 mL/g, extraction time of 26 minutes, and ethanol concentration of 26.12%. Validation under these conditions yielded a TPC of 152.26 mg GAE/g DE and a TFC of 68.59 mg QE/g DE, with percentage errors of âˆ’7.7% and 3.5%, respectively, demonstrating excellent agreement with the predicted values.